Discrepancy of clinical, laboratory and instrumental picture in patients with pulmonary embolism - A. G. Pronin; A. R. Rakhmatullina; D. K. Glukhov (Вестник медицинского института «Реавиз»: Реабилитация, врач и здоровье, 2022)
The discrepancy of echocardiographic signs of right ventricular overload with the clinical picture and the level of plasma troponin concentration may underestimate the severity of the condition and lead to an inadequate choice of therapy, since all these parameters are currently determining the tactics of treatment of patients.Objective: to assess the prevalence and clinical characteristics of patients with pulmonary embolism with inconsistency of clinical, laboratory and instrumental picture.Material and methods. The course of the disease of 456 patients with pulmonary embolism was analyzed. 21 patients had a fatal outcome, the rest recovered. All patients underwent general clinical and biochemical blood tests, determination of the level of D-dimer and troponin, electrocardiography, echocardiography, ultrasound of the veins of the lower extremities, CT angiopulmonography, analysis of the results obtained.Results. It was found that among patients with high- and moderate-risk pulmonary embolism, women more often than men have an increase in the plasma concentration of troponin levels by 2.4 times, as well as a 3-fold discrepancy in the clinical and laboratory-instrumental picture with the presence of signs of right ventricular overload according to echocardiography data, which appear in dynamics. The phenomenon of "delayed echocardiography signs of overload of the right heart" is recorded in 0.8% of all patients with pulmonary embolism. At the same time, in patients with a high risk of early pulmonary embolism – associated death, its occurrence is 2.1%, and in patients with a moderately high risk – 4.4%. When comparing the prevalence of clinical and instrumental symptoms of pulmonary embolism in these patients with the data of patients with high and moderate risks of early death from pulmonary embolism, no statistically significant differences were found, including in terms of echocardiography in dynamics. The delay of еchocardiography signs of overload of the right parts of the heart" by 12–36 hours from the clinical picture, including in patients with hemodynamically significant pulmonary embolism, can be detected only with a series of еchocardiography, which allows, if necessary, timely review scope of treatment. In patients with pulmonary embolism with a pronounced lesion of the pulmonary artery, due to the rapidly progressing course of the disease, it is possible that the еchocardiography criteria of the disease do not have time to develop. In this case, an assessment of the stroke volume may play an important role, hover this parameter is non-specific for this disease.